Notion of Conflict : A Selection of Contemporary Canadian Art. - Burns, Bill; David, Alexandre; Douglas, Stan; Déry, Louise; Fuchs, Rudi H.; Houle, Robert; Lum, Ken; Magor, Liz; Mignot, Dorine; Snow, Michael; Steinman, Barbara; Stevenson, Sarah; et al. (Amsterdam : Stedelijk Museum Amsterdam, 1995)
Blain, Dominique ; Burns, Bill ; David, Alexandre ; Douglas, Stan ; Houle, Robert ; Lum, Ken ; Magor, Liz ; Steinman, Barbara ; Stevenson, Sarah ; Snow, Michael ; Wainio, Carol ; Wall, Jeff ; Wallace, Ian
biografie
Notion of Conflict : A Selection of Contemporary Canadian Art, Stedelijk Museum Amsterdam, 1995
Engels
boek
Keywords: Canada